IMPLEMENTASI PEMBIAYAAN GADAI EMAS DALAM MENINGKATKAN PROFITABILITAS LEMBAGA KEUANGAN SYARIAH - Najmul Hidayat; Aang Kunaifi (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2023)
Selection of the right product in the Islamic financial institution industry can support the achievement of profit targets. One product that has a lot of interest is pawn gold, which is technically quite simple. This article aims to determine the procedure and mechanism for financing pawn gold in Islamic financial institutions and explain the profit setting system for pawning gold financing that can increase profitability. The results of this study indicate that the procedure, mechanism, and profit determination system for sharia pawn products (rahn) are very easy to understand and easy to implement. In fact, it is also easily understood by customers, so that in preference it becomes the main choice for the community. The implication is that this product can be used as a mainstay for Islamic financial institutions to increase profitability. So it is hoped that this product can be developed and disseminated massively to the public.